(untitled) (Revista Brasileira Multidisciplinar, 2019)
The objective of this study was to evaluate the growth, development and productive aspects of strawberry plants submitted to inoculation of Azospirillum brasilense, Bacillus amyloliquefaciens and Trichoderma asperellum with and without association with Silicon (Si). The experimental design was randomized blocks, with eight treatments, three blocks, three replicates per treatment for each block. Growth and development evaluations were performed at 30 and 60 days after transplanting (DAT) of the seedlings. For the evaluations of the productive aspects, the ripe fruits collected were submitted to the physical-chemical analyzes. The dry biomass accumulation was determined by dry mass of the shoot (MSA), dry mass of the crown (MSC), dry mass of the roots (MSR) and total dry mass (MST). At 30 DAT, no significant difference was observed between treatments. At 60 DAT the treatments B. amyloliquefaciens (T3) and Si (T5) had the highest chlorophyll indexes (CI). The treatments T. asperellum and Si (T6), T3 and T5 presented the highest averages for MSA, whereas the T5 treatment had the highest mean for MSC and the T6 treatment presented the highest mean for MSR and MST. It was concluded that the treatments influenced the growth, development and accumulation of dry biomass in the strawberry, not having influence on the physical-chemical parameters of the fruits.